[Aetas ; Philippine Eagle ; Mamang sorbetero [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Visit to the Aeta resettlement area in Buhawon Zambales. Interview with Aeta children about their experiences during the Pinatubo eruption; tells us why the Philippine eagle is now an endangered species; visit of a local ice cream maker to see how "dirty ice cream" is made.